Peran Lubna Bimbel dalam Mengembangkan Kecakapan Calistung Anak pada Jenjang TK-SD Kelas 3 - Soraya, Zulfatus; Syarifuddin, Muhammad Rifqi; Putri, Nabilla (J-PGMI: Jurnal Pendidikan Guru MI, 2025)
Calistung Tutoring (Read, Write, Count) is a non-formal educational institution that applies additional and complementary learning for children with basic knowledge of reading, counting, writing and counting. This study aims to find out how the role of Lubna Bimbel Karangwangkal in accompanying and developing calistung skills in children around their village and outside the village. This research uses a qualitative approach. Data collection techniques consist of observations and interviews which are then analyzed into conclusions. The results of this study show that 1) Lubna Bimbell Karangwangkal is able to develop children's learning skills at the age of kindergarten-elementary school grade 3 using modules made by themselves, 2) Parents feel helped by the existence of Lubna Bimbel, 3) Lubna Bimbel apart from being a calistung tutoring, also becomes a daycare place when learning is complete, 4) Many parents have entrusted their children with names to follow the tutoring, 5) The implementation of tutoring at Lubna Bimbel is very effective and efficient so that the results obtained by children look significant from the learning results 6) The evaluation carried out by Lubna Bimbel is different from other tutors, namely using practice questions 1 at the top level which makes children master learning at the upper level.